The Use of Elllo Podcast Application to Enhance Students Listening Skill - Umi Kalsum; Hassan, Muhammad Hassan; Donny Adiatmana Ginting (Institut Agama Islam Negeri Palopo, 2024)
The purpose of this study was to determine use of the Elllo English learning Podcast Application can improve listening skills of seventh grade students at MTS Darul Ilmi Pangkalan Brandan. In this study, researchers used a quantitative experimental research method with type of true experimental by using two classes, namely class VII-1 as Experiment class and class VII-2 as Control class. In this study, researchers used a total sampling technique that used all class students of VII-1 and VII-2 classes totalling 45 students. In conducting research, researchers conducted pre-test and post-test in both classes. In conducting research, researchers conducted pre-test and post-test in both classes. The results of the average value of research obtained during pre-test of experimental class were 52.39 and control class was 51.81, both of which were included in poor category. After treatment, average post-test score obtained by experimental class was 72.82 which was included in good category and control class was 65.68 which was included in low category.